Impact of degrading air quality on mode choice and emissions – Study of ten global cities. (2022) - Jain, Deepty; Bhatnagar, Smriti; Sachdeva, Kamna
Abstract: People are most exposed to ambient air quality while travelling. They are therefore likely to change their travel choices to minimize exposure. We assess the impact of degrading air quality on modal shares and equivalent CO2 emissions per capita per trip for ten global cities using a scenario-based approach. The scenarios are based on literature that are used to estimate the likely change in modal share and average trip length by mode for ten global cities. The study shows that the non-motorized transport and public transport (PT) share is likely to decrease and personal vehicle share is likely to increase in the selected cities of high-income countries (HIC). In middle-income countries (MIC), both PT and personal vehicle share is likely to increase. The expected absolute change in emissions per trip is likely to be higher in the HIC cities than in the MIC cities. However, the existing air quality levels are poor in the MIC cities imposing a greater threat on the existing modal shares and emissions per capita per trip. The study also shows that the increase in income in the MIC cities shall result in an increasing impact of degrading air quality on modal share.